Splint Therapy Using CAD-CAM Technology for Temporomandibular Joint Dysfunction - Aliev Navruz Khasanovich (American Journal of Biology and Natural Sciences, 2024)
The aim of the study was to evaluate possible applications of muscle relaxation splints made with a milling method (with CAD/CAM technologies) for correction of the temporomandibular joint (TMJ). Materials and Methods. We studied 47 patients with TMJ disc displacement with reduction that causes the lower jaw articulation disorders. All patients underwent axiographic investigation before, in the course of (every 3 weeks), and after the treatment. In group 1 (n=22) we used muscle relaxation splints made in a mechanical articulator, in group 2 (n=25) splints were modeled in a virtual articulator in accordance with axiographic findings. Results. The results of treating patients with subluxation of the TMJ articular disc with muscle relaxation splints made with mechanical and virtual articulators showed that the use of a virtual articulator resulted in minimal frequency of positioning errors in the articulator interframe space. The study also revealed that higher accuracy of location of virtual models in accordance with an individual location of joint mechanisms of an articulator. We developed a method of loading individual joint trajectories of the lower jaw when the articulation of the latter is impaired. It helped to considerably reduce inaccuracies of splint modeling that occur when a standard mechanical face bow made with mechanical articulators is used. Conclusion. For patients with TMJ disc displacement with reduction treatment with milled splints made in a virtual articulator is more preferable. The developed algorithm of loading individual joint trajectories of the lower jaw movements and occlusion contacts according to axiographic findings during the process of modeling muscle relaxation splints can enhance the quality of treating patients with dearticulation